Pemetaan dan Analisis Tempat Penampungan Sampah Sementara Menggunakan Sistem Informasi Geografis di Kecamatan Mataram, Kota Mataram - Wahyudin Wahyudin; Erlan Siswandi (Jurnal Serambi Engineering, 2021)
The transportation of waste from the Temporary Waste Shelter (TWS) to the Final Processing Site (FPS) needs to be carried out to avoid the accumulation of waste in the TWS, because it has the potential to endanger the environment and health. This study aims to determine the distribution, capacity, service radius, and technical feasibility of TWS using a Geographic Information System (GIS), and to determine the level of need for TWS facilities in the Mataram District. This research is a descriptive observational study, where the researchers conducted a field survey by means of observation, plotting coordinates with GPS, and measuring waste generation on the specified respondents. The data is processed and analyzed spatially and normatively, then described. The results showed that there were 8 points TWS in Mataram District, with an uneven distribution in each village, namely 3 wards that did not have a formal TWS. The capacity of the existing TWS is adequate for containing waste from its coverage service, as well as the condition of the TWS in general is good but they need to be repaired and maintained. The need TWS in Mataram District is 16 units where 8 of them have being existing. The remains for additional TWS is 8 units those can be placed in each village, especially in 3 villages that do not yet have TWS, namely Punia, Pagesangan Barat, and Pagesangan Timur